A FRET flow cytometry method for monitoring cytosolic and glycosomal glucose in living kinetoplastid parasites - Voyton, Charles M.; Qiu, Yijian; Morris, Meredith T.; Ackroyd, P. Christine; Suryadi, Jimmy; Crowe, Logan; Morris, James C.; Christensen, Kenneth A. (PLOS Neglected Tropical Diseases, 2018)
The bloodstream lifecycle stage of the kinetoplastid parasite Trypanosoma brucei relies solely on glucose metabolism for ATP production, which occurs in peroxisome-like organelles (glycosomes). Many studies have been conducted on glucose uptake and metabolism, but none thus far have been able to monitor changes in cellular and organellar glucose concentration in live parasites. We have developed a non-destructive technique for monitoring changes in cytosolic and glycosomal glucose levels in T. brucei using a fluorescent protein biosensor (FLII12Pglu-700μδ6) in combination with flow cytometry. T. brucei parasites harboring the biosensor allowed for observation of cytosolic glucose levels. Appending a type 1 peroxisomal targeting sequence caused biosensors to localize to glycosomes, which enabled observation of glycosomal glucose levels. Using this approach, we investigated cytosolic and glycosomal glucose levels in response to changes in external glucose or 2-deoxyglucose concentration. These data show that procyclic form and bloodstream form parasites maintain different glucose concentrations in their cytosol and glycosomes. In procyclic form parasites, the cytosol and glycosomes maintain indistinguishable glucose levels (3.4 ± 0.4mM and 3.4 ± 0.5mM glucose respectively) at a 6.25mM external glucose concentration. In contrast, bloodstream form parasites maintain glycosomal glucose levels that are 1.8-fold higher than the surrounding cytosol, equating to 1.9 ± 0.6mM in cytosol and 3.5 ± 0.5mM in glycosomes. While the mechanisms of glucose transport operating in the glycosomes of bloodstream form T. brucei remain unresolved, the methods described here will provide a means to begin to dissect the cellular machinery required for subcellular distribution of this critical hexose.